HOMOGENEOUS OPERATORS AND WEIGHTED SHIFT WITH MULTIPLIERS - Abedrahaman, Bashir (Journal of Statistics and Actuarial Research, 2022)
In this paper we show that a homogenous operator is unitary and a reducible homogenous weighted shift is un weighted bilateral shift, also a projective representation is irreducible, and the quasi-invariant is equivalent to a unitary representation.